Texts as events – or how to account for descriptions as intervention - Olander, Sissel (STS Encounters, 2016)
From the introduction: In this article I problematize how texts are sometimes cast as potent interventionists in cultural-analytical and constructivist social research. I engage with two different articles, which discuss texts as interventions. One is an article by Signe Vikkelsø titled: “Description as Intervention - Engagement and Resistance in Actor-Network Analyses” (2007). The other is an article by Brit Winthereik and Helen Verran titled “Ethnographic stories as Generalisations that Intervene” (2012). In both articles the authors propose strategies for writing up accounts. The purpose of these proposed strategies is to induce the text with certain qualities, in order to enhance the interventionist powers of the texts. I will inspect these strategies as particular research set-ups, and challenge how the process of writing up the analysis and account is continually conflated with claims about how the text will intervene in some more or less specified future. I do so by exploring descriptions and texts as events, and by inspecting the proposed research strategies as if they were in fact experimental research set-ups. To this end I draw on prevailing ideas about the relation between program and experiment in constructive design research, and on the work of philosopher of science Hans-Jörg Rheinberger.